Unfinished Dreams : Community Healing and the Reality of Aboriginal Self-Government - Warry, Wayne (Book collections on Project MUSE., 1998)
Wayne Warry argues that Aboriginal self-government can be realized only when individuals are secure in their cultural identity and can contribute to the transformation of their communities.